The Discursive Ethos: From The Social Conception of Language to The Social Conception of the Subject - Laamiri, Karima (European Scientific Journal, ESJ, 2020)
The discursive ethos is a notion that is primarily related to communication including verbal interactions. Indeed, language is not only a simple means of individual expression but it reflects the linguistic and extralinguistic side of the talking subject. This social conception of language has developed over the years to show that language activity is closely linked to the social and societal activity of individuals. In an interactive process, as in the case of political communication, interlocutors are led to persuade their audience through a positive self-image. It is thus that projecting a successful ethos becomes primordial. Indeed, the study of the speaking subject in the political discourse shows that the speaker is part of his speech. In other words, he marks its subjectivity through linguistic processes that arise throughout his communication. In addition, the political actor reflects both the image of his political group and that of his social group. And this is through the use of the personal pronoun "we" which gathers three instances: political, citizen and patriotic. It is in this context that this research is carried out from a sociodiscursive approach that involves the linguistic aspect and the social aspect of language.